Factors Influencing Stock Price Variability of Commercial Banks in Nepal (The Journal of Economic Concerns, 2022)
This study investigates the impact of variables such as Dividends Per Share (DPS), Earnings Per Share (EPS), Price-Earnings Ratio (PER), and Net Worth Per Share on the Market Price Per Share of Nepalese commercial banks. The panel data (40 observations) of four commercial banks have been used to assess the association and impact of determinants of stock price behavior. In this study, secondary panel data covering ten years (2011/2012-2020/2021) has been used. According to the findings of this study, Earnings per share has a significant positive relationship with the Dividends Per Share and Price-Earnings Ratio but a negligible positive relationship with Market Price Per Share, Earnings Per Share, and Net Worth Per Share of commercial banks.